2021
DOI: 10.3389/fphys.2021.761481
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanisms of Gastric Volume-Restriction Bariatric Devices

Abstract: Obesity is a chronic disease that affects over 795 million people worldwide. Bariatric surgery is an effective therapy to combat the epidemic of clinically severe obesity, but it is only performed in a very small proportion of patients because of the limited surgical indications, the irreversibility of the procedure, and the potential postoperative complications. As an alternative to bariatric surgery, numerous medical devices have been developed for the treatment of morbid obesity and obesity-related disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…51 For gastric banding, the effect on body weight might be assumed to depend on the gastric restriction but appears to involve additional mechanisms. 52 Vertical sleeve gastrectomy (SG) and gastric bypass (Roux-en-Y gastric bypass, RYGB) have additional metabolic effects, and have been shown to improve T2D within days after surgery, even before significant weight loss occurs. 53 While the mechanisms may be multifactorial, an increase in GLP-1 levels and bile acids (at least in rodents) may be involved.…”
Section: Gastrointestinal Bypass Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…51 For gastric banding, the effect on body weight might be assumed to depend on the gastric restriction but appears to involve additional mechanisms. 52 Vertical sleeve gastrectomy (SG) and gastric bypass (Roux-en-Y gastric bypass, RYGB) have additional metabolic effects, and have been shown to improve T2D within days after surgery, even before significant weight loss occurs. 53 While the mechanisms may be multifactorial, an increase in GLP-1 levels and bile acids (at least in rodents) may be involved.…”
Section: Gastrointestinal Bypass Proceduresmentioning
confidence: 99%
“…The effectiveness of bariatric surgery has triggered many attempts to identify the mechanisms involved 51 . For gastric banding, the effect on body weight might be assumed to depend on the gastric restriction but appears to involve additional mechanisms 52 . Vertical sleeve gastrectomy (SG) and gastric bypass (Roux‐en‐Y gastric bypass, RYGB) have additional metabolic effects, and have been shown to improve T2D within days after surgery, even before significant weight loss occurs 53 .…”
Section: Strategies To Utilise Endogenous Glp‐1 Therapeuticallymentioning
confidence: 99%
“…On the other side, studies in adjusted gastric banding (AGB) reported that AGB has no influence or even delays gastric emptying ( 11 , 12 ). Some GI devices were also reported to decrease GI emptying although the bariatric effects are good ( 13 ).…”
Section: Introductionmentioning
confidence: 99%